HOW GENDER INFLUENCES CALCULATIONS AND epistemic RELATIONS - Augusto Viglioni, Torquato (Revista Gênero e Interdisciplinaridade, 2022)
In the work “Epistemic’s Injustice” by Miranda Fricker, the ideas of epistemic injustices and epistemic virtues are developed from a conception of justice that assumes that injustices are common and justice is their correction. Thus, the normal would be the unjust epistemic relationships and the correction would be the virtues. However, when describing and conceptualizing epistemic injustices, the author differentiates and separates them into testimonial and hermeneutic injustices, despite the fact that both originate and are based on relations of social power. Witness injustice is conceptualized as an unfair epistemic calculation influenced by identity prejudices derived from social power. Hermeneutic injustice is conceptualized as a social structural gap, that is, inserted in the social base. When conceptualizing the epistemic virtue, the philosopher uses the idea of ​​correcting justice of injustices, thus, each virtue is exercised in order to correct and to the extent of the injustices that they aim at. Witness injustices would be corrected by virtuous actions in the witness sphere through the virtuous listener who would be sensitive to social relations, to ethical duty and, thus, would be able to give credibility to the speaker in a fair way. However, despite defending the dosimetry of epistemic virtues and emphasizing that group political action is needed for social change, the philosopher argues that the primary ethical role of hermeneutic justice is to mitigate the negative impact of hermeneutic injustice on the speaker. Based on the author’s conceptions that structure epistemic injustices - social power - it is possible to make a link with Silvio Almeida, this link allows the construction of an argument about how gender is a factor that influences epistemic relations. From this premise, it is possible to infer that discrediting or excessive credibility is used as a means/mode of domination and social perpetuation.